PERANCANGAN WEBSITE MEMBANGUN SISTEM PENJUALAN SEPATU PADA PT. TOMKINS - Adi Prasetyo (Universitas PGRI Yogyakarta, 2022)
Product sales is an important activity in the development of the company which is an important aspect in the development of the company. The problems that have arisen in the pandemic era since March 2018, the large number of large outlets such as Matahari and the Hero group have made the turnover of PT. Tomkins has decreased drastically especially since the workers were laid off. In April 2020 when faced with the problem of declining marketing from large outlets. In dealing with these problems, other ways are needed to run the business, so it is necessary to design a system that is used to run a business. The waterfall method is used to design the system, while the data collection technique uses research methods with observations, interviews, and library studies. And the database development tool uses the MySQL programming language. The purpose of this research is to design a business system in order to get partners as resellers so that sales can be further increased and facilitate customer service and transactions without having to come directly to a physical store. The result of this research is to provide an alternative business concept with a cooperation system in sales. The application aims to create cooperation and increase company sales..